2021
DOI: 10.1111/pce.14103
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress pathway mediates the early heat stress response of developing rice seeds

Abstract: A transient heat stress occurring during early seed development in rice (Oryza sativa) reduces seed size by altering endosperm development. However, the relationship between the timing of the stress and specific developmental stage on heat sensitivity is not well-understood. To address this, we imposed a series of non-overlapping heat stress treatments and found that young seeds are most sensitive during the first two days after flowering. Temporal transcriptome analysis of developing, heat stressed (35 C) see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 115 publications
2
16
0
Order By: Relevance
“…This may suggest that correct folding of γ-zeins is more sensitive to heat stress and this in turn has negative effects on the 19 kDa α-zeins that directly interact with the outer PB layer mainly constituted by γ-zeins. Upon treatment of developing rice seeds with moderate heat stress (35°C) at 1 or 2 DAF, transient OsbZIP50 transcription and splicing were enhanced within 1 h in the endosperm, with consistent increase in transcripts of folding factors, including BIP and PDI isoforms ( Sandhu et al, 2021 ). The bZIP28 branch of UPR was instead not activated.…”
Section: Upr and Seed Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that correct folding of γ-zeins is more sensitive to heat stress and this in turn has negative effects on the 19 kDa α-zeins that directly interact with the outer PB layer mainly constituted by γ-zeins. Upon treatment of developing rice seeds with moderate heat stress (35°C) at 1 or 2 DAF, transient OsbZIP50 transcription and splicing were enhanced within 1 h in the endosperm, with consistent increase in transcripts of folding factors, including BIP and PDI isoforms ( Sandhu et al, 2021 ). The bZIP28 branch of UPR was instead not activated.…”
Section: Upr and Seed Heat Stressmentioning
confidence: 99%
“…It was therefore concluded that IRE1-mediated ER stress response participates in early heat stress response in rice seeds, although whether this is a direct result of storage protein misfolding remains to be determined. Furthermore, jasmonic acid biosynthesis and signaling genes were also induced, and treatment with the hormone induced IRE1-mediated UPR response, thus indicating relationships between UPR and jasmonic acid that however remain to be elucidated ( Sandhu et al, 2021 ).…”
Section: Upr and Seed Heat Stressmentioning
confidence: 99%
“…We further filtered these genes based on their expression in developing grain using public dataset (GSE6893) and identified 10 genes that are preferentially expressed in grains. For the genes associated with SNP detected under HS treatment, we examined their expression in a comparable HS treatment in a public dataset ( Sandhu et al., 2021 ). We identified 18 genes to be differentially expressed in response to HS ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, studies have shown that mitogen-activated protein kinase (MAPK) modules play critical roles in the transduction of environmental and developmental signals ( Jagodzik et al, 2018 ). A lot of studies in plants have described the role of endoplasmic reticulum (ER) stress signaling and UPR in regulation of HSFs and HSPs ( Hayashi et al, 2012 ; Mittler et al, 2012 ; Sandhu et al, 2021 ). We found that upregulated DEGs in leaf and root ( Figures 8A,B ) were all enriched in the pathway “Protein processing in endoplasmic reticulum,” which suggests that the expression of genes related to protein processing in the endoplasmic reticulum is significantly upregulated when pepper is subjected to heat stress, which may be involved in the process of pepper’s response to heat stress.…”
Section: Discussionmentioning
confidence: 99%